The Clinical Significance of Exhaled Nitric Oxide in Asthma - Sachin Pendharkar; Sanjay Mehta (Canadian Respiratory Journal)
Asthma is an inflammatory disease of the airways, for which many therapeutic options are available. Guidelines for the management of asthma suggest a stepwise approach to pharmacotherapy based on assessment of asthma severity and control. However, the assessment of asthma control presently relies on surrogate measures, such as the frequency of symptoms or the frequency of use of short-acting beta2-adrenergic agonists. There is no simple, noninvasive technique for the assessment of severity of actual airway inflammation in asthma. The collection and analysis of nitric oxide (NO) levels in exhaled breath has recently become feasible in humans. Based on increased exhaled NO (eNO) levels in patients with asthma, eNO analysis has been proposed as a novel, noninvasive approach to the assessment and monitoring of airway inflammation, and as a basis for adjustments in asthma therapy. In the present paper, the relationship of elevated eNO levels in asthma with inflammatory, physiological and clinical markers of asthma in adults was reviewed. Use of eNO is a promising tool for diagnosing asthma, for monitoring asthma control and for guiding optimal anti-inflammatory asthma therapy. However, because of many unresolved questions, eNO cannot be recommended at present for routine clinical management of adults with asthma.